Personal and Reflective Epistemology in Pre-Service Teacher Education - Heiney-Smith, Jill (International Dialogues on Education Journal, 2018)
Teacher preparation programs aim to provide pedagogical skills for knowledge development and critical thinking. Yet teacher candidates themselves have views and understandings of the very nature of knowledge, or epistemology, which might inhibit or advance their development as teachers. This paper begins with an overview of Kitchener’s (1983) model for cognitive processing and later work in epistemological development, The Reflective Judgment Model (1994, 2004). Next, a presentation of research in teacher candidate epistemology in Poland is compared with a study of teacher candidate perceptions in Singapore, both grounded by Kitchener’s model of knowledge development. Finally, a comprehensive research review by Sleeter (2000) reveals the limitations of such studies in the application to historically under-served students and teachers of color in the United States.